PERANCANGAN APLIKASI POINT OF SALE PANDITA COFFEE BERBASIS WEB DENGAN KOMBINASI MODEL SDLC WATERFALL - Azizah, Fuza (STMIK KAPUTAMA, 2022)
Technology has grown fast, especially in the field of data technology to support human activities in order to create efficiency. In the current work environment, technology is the main principal in carrying out all forms of work using existing energy sources on computers and internet networks. Point Of Sale or abbreviated (POS) can be translated as a cashier system, is a sales-oriented activity that occurs in the retail business sector. This POS is really worth it because POS is a terminal that accepts money from customers. For business owners, cash in is a simple indicator of business income. One of the website-based application systems needed on Pandita Coffee is Point Of Sale, because at Pandita Coffee the cashier system still uses the manual method. A system with a dynamic level, while the available budget and development time are very limited. Data collection methods in this study are literature study, interviews, observation, and data analysis. The design system development method used by researchers to design a Point Of Sale Application System with a waterfall model defined by Pressman is a classical model in forming software with sequential properties. The model is one-way from initial preparation to treatment. In making the Point Of Sale system, it is very helpful in business processes, especially in processing transactions, inventory, and financial reports.